Perceptions of the Changing Healthcare Environment: A Florida Perspective - Aaron Spaulding; Hanadi Hamadi; D. Rob Haley; Mei Zhao; Clark (Moody) (University of North Florida, 2015)
This study reviewed public perceptions of healthcare, including the public's opinions of healthcare reform. The study's objective was to examine how opinions are affected by individual differences such as age, income, race, and current insurance. It used telephone survey responses from the citizens of Florida to provide a more empirical look at the views of the population. Overall, the study findings provided important insight into the perceptions of Floridians of important components of the Patient Protection and Affordable Care Act (ACA) including cost, affordability, Medicaid expansion, and universal access to care. The results of this study indicate that whereas income, type of insurance held, race, education, and age have some impact on response to the statements posed, party affiliation is the best indicator of individuals' perceptions of the policies. In addition, results suggest that policymakers should consider more effective and targeted ACA educational campaigns for those populations that are older, more educated, and with higher incomes. They also should consider identifying and implementing opportunities to expand the Medicaid program because there is such broad support for its expansion.